A Food Literacy-Based GAMI Program: Improving Awareness of Fish Consumption in Early Childhood Nutrition - Noviana Mustapa; Siti Aisyah; Erie Siti Syarah; Mia Andriani; Millatina Nur Afiah Djamal; Agnes Puspitasari Sudarmo; Hasrianti Hasrianti; Musakkid Himphinit (Atfaluna: Journal of Islamic Early Childhood Education, 2026)
Purpose – This study aims to examine teachers’ and parents’ knowledge, attitudes, and practical skills related to fish consumption for early childhood nutrition through a community service-based educational intervention, the food-literacy-based Gerakan Anak Makan Ikan (GAMI) program. Design/methods/approach – Aone group pre-test post-test design was used with participatory and educational approaches. The participants were 100 respondents, consisting of 50 preschool teachers and 50 parents of preschool children in Babakan, Pangandaran, West Java. Participants were selected purposively based on their roles in early childhood education and care. Data were collected using questionnaires and analysed descriptively and inferentially with a paired-samples t-test. The intervention consisted of food literacy education, fish processing demonstrations, mentoring, and practical implementation at home and in early childhood education settings. Findings – The results showed a statistically significant improvement after the implementation of the food-literacy-based GAMI program. The mean score across the five measured aspects increased from 54.20 ± 3.70 before the program to 83.20 ± 1.92 after the intervention, with a mean improvement of 29.00 ± 2.24 points. A paired samples t-test conducted at the aspect level showed that this increase was statistically significant, t(4) = 29.00, p < 0.001, 95% CI [26.22, 31.78]. Research implications/limitations – The results suggests that the program was associated with meaningful gains in understanding fish benefits, animal protein and stunting prevention, fish selection, child friendly fish meal processing, and positive attitudes toward fish consumption. Practical implications/Originality – These findings provide preliminary evidence that the food-literacy-based GAMI program may serve as a contextual and practical model for promoting fish consumption and supporting early childhood nutrition in Indonesian coastal communities.